Recognition of COVID-19 with occupational origin: a comparison between European countries - Nys, Evelien; Pauwels, Sara; Ádám, Balázs; Amaro, João; Athanasiou, Athanasios; Bashkin, Osnat; Bric, Tatjana Kofol; Bulat, Petar; Caglayan, Cigdem; Guseva Canu, Irina; Cebanu, Serghei; Charbotel, Barbara; et al. (BMJ, 2023)
Objectives This study aims to present an overview of the formal recognition of COVID-19 as occupational disease (OD) or injury (OI) across Europe. Methods A COVID-19 questionnaire was designed by a task group within COST-funded OMEGA-NET and sent to occupational health experts of 37 countries in WHO European region, with a last update in April 2022. Results The questionnaire was filled out by experts from 35 countries. There are large differences between national systems regarding the recognition of OD and OI: 40% of countries have a list system, 57% a mixed system and one country an open system. In most countries, COVID-19 can be recognised as an OD (57%). In four countries, COVID-19 can be recognised as OI (11%) and in seven countries as either OD or OI (20%). In two countries, there is no recognition possible to date. Thirty-two countries (91%) recognise COVID-19 as OD/OI among healthcare workers. Working in certain jobs is considered proof of occupational exposure in 25 countries, contact with a colleague with confirmed infection in 19 countries, and contact with clients with confirmed infection in 21 countries. In most countries (57%), a positive PCR test is considered proof of disease. The three most common compensation benefits for COVID-19 as OI/OD are disability pension, treatment and rehabilitation. Long COVID is included in 26 countries. Conclusions COVID-19 can be recognized as OD or OI in 94% of the European countries completing this survey, across different social security and embedded occupational health systems.